Public Goods Access and Juvenile Sex Ratios in Rural India: Evidence from the 1991 and 2001 Village Census Data - Anil B. Deolalikar; Rana Hasan; Rohini Somanathan (Asian Development Bank (ADB), 2009)
We use village level data from the 1991 and 2001 Indian Censuses to examine how the availability of health facilities and safe drinking water at the village level affect juvenile sex ratios. In addition to controlling for village fixed effects in our estimating equation of the juvenile sex ratio, we also allow villages to be heterogeneous in terms of how their juvenile sex ratios respond to the availability of health facilities and safe drinking water. A key result we obtain is that although the presence of public health facilities does not exert a positive, significant effect on juvenile sex ratios on average, they do so in villages where the problem of discrimination against girls is most acute, i.e., in villages at the 0.10 and 0.25 quantiles of the conditional juvenile sex ratio distribution. Thus public policy can be an effective tool in improving gender balance in cases where it is most needed.
hdl:11540/1818
Keywords: 330; Gesundheitsversorgung; Wasserversorgung; Geschlecht; Öffentliche Güter; Ländlicher Raum; Indien